Chymase Dependent Pathway of Angiotensin II Generation and Rapeseed Derived Peptides for Antihypertensive Treatment of Spontaneously Hypertensive Rats - Baranowska, Iwona; Gawrys, Olga; Roszkowska-Chojecka, Malwina M.; Badzynska, Bozena; Tymecka, Dagmara; Olszynski, Krzysztof H.; Kompanowska-Jezierska, Elzbieta (Frontiers in Pharmacology, 2021)
The contribution of chymase, one of the enzymes responsible for angiotensin II generation in non-ACE pathway, remains unclear in the development of hypertension. The aim of the study was to investigate chymase inhibition as potential antihypertensive therapy in spontaneously hypertensive rats (SHR). To block chymase we employed chymostatin, a commercial inhibitor, and new analogues of rapeseed-derived peptides, VWIS and RIY. These simple and easy to obtain peptides not only block chymase, but also possess weak activity to inhibit ACE. This is a first attempt to evaluate the impact of chronic administration of selected inhibitors on blood pressure of SHR in two phases of hypertension. Male SHR (6 or 16 weeks old) were treated daily for two weeks with chymostatin (CH; 2 mg/kg/day), the peptides VWIS (12.5 mg/kg/day) or RIY (7.5 mg/kg/day); control groups received chymostatin solvent (0.15 % DMSO in saline) or peptide solvent (saline). The substances were administered intravenously to conscious animals via a chronically cannulated femoral vein. Systolic blood pressure (SBP) was measured by telemetry. Metabolic parameters were measured weekly, and tissue samples were harvested after two weeks of treatment. None of the administered chymase inhibitors affected the development of hypertension in young rats. Only RIY exhibited beneficial properties when administered in the established phase of hypertension: SBP decreased from 165±10 to 157±7 mmHg while the excretion of nitric oxide metabolites increased significantly. The glomerulosclerosis index was lower after RIY treatment in both age groups (significant only in young rats 0.29±0.05 vs 0.48±0.04 in the control group; p<0.05). Hence, it seems that peptide RIY exhibits some positive effect on renal morphology. The results obtained suggest that the peptide RIY may be a useful tool in the treatment of hypertension, especially in cases when ACE inhibitors are not effective.